2021
DOI: 10.3390/polym13050696
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Chitosan–Polylactate Fabricated Plastic Film and Its Application on the Preservation of Fish Fillet

Abstract: This research prepared chitosan–PLA plastic films by extrusion, analyzed the physical and mechanical properties and antibacterial activity of the fabricated plastic films, and used them to preserve grouper fillet. We added chitosan (220 kDa, 93% DD) in the weight ratio of 0.5–2% into the PLA to prepare the chitosan–PLA films. With the increasing chitosan dosage, both the water vapor transmission rate and moisture content of chitosan–PLA films increased. Among the three doses of chitosan (0.5%, 1%, and 2%) adde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…As the mechanism of chitosan antimicrobial action is mediated through the electrostatic interaction between the protonated amine residues in the chitosan molecule and the negatively charged groups on the bacterial surface [12,17], the biocidal effect of chitosan film, as proposed by Zimet et al [18], may be due to the release of protonated glucosamine fractions from the biopolymer. However, the larger molecular weight and poor water-solubility of the chitosan (220 kDa) used in our previous chitosan-PLA film [16] may have limited the release of glucosamine residues, and thus limited the preservative effect on grouper fillet at room temperature. Only low-temperature storage could clearly show the ability of this film to extend the shelf-life of grouper [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the mechanism of chitosan antimicrobial action is mediated through the electrostatic interaction between the protonated amine residues in the chitosan molecule and the negatively charged groups on the bacterial surface [12,17], the biocidal effect of chitosan film, as proposed by Zimet et al [18], may be due to the release of protonated glucosamine fractions from the biopolymer. However, the larger molecular weight and poor water-solubility of the chitosan (220 kDa) used in our previous chitosan-PLA film [16] may have limited the release of glucosamine residues, and thus limited the preservative effect on grouper fillet at room temperature. Only low-temperature storage could clearly show the ability of this film to extend the shelf-life of grouper [16].…”
Section: Introductionmentioning
confidence: 99%
“…Some types of chitosan-PLA films have been developed, including chitosan/poly (vinyl alcohol) PLA film [14] and chitosan/polyethylene glycol PLA film [15]. In our previous report, we prepared a chitosan-PLA composite film for the preservation of fish fillets [16]. As the mechanism of chitosan antimicrobial action is mediated through the electrostatic interaction between the protonated amine residues in the chitosan molecule and the negatively charged groups on the bacterial surface [12,17], the biocidal effect of chitosan film, as proposed by Zimet et al [18], may be due to the release of protonated glucosamine fractions from the biopolymer.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Bonilla et al [33] observed that the addition of 5% or 10% chitosan did not affect the thermal properties of PLA, but decreased film flexibility, while Spiridon et al [34] realized green materials by melt processing with relatively good mechanical and thermal-mechanical properties by incorporating keratin in PLA/CS blends, followed by changes evaluation after accelerating weathering conditions. Extruded films of PLA with 0.5-2% CS were found promising for preserving refrigerated fish [35]. Introduction of chitosan into plasticized PLA with tributyl o-acetyl citrate (ATBC) conducted to antimicrobial materials with tensile strength at break of~24 MPa, and water vapor transmission rate of 43.91 g m −2 day −1 properties [36].…”
Section: Introductionmentioning
confidence: 99%
“…PLA is a commonly used polymer for packaging because it has mechanical, thermal, and barrier properties comparable to the most used synthetic plastics, having the advantage of being biodegradable and obtained from renewable sources [ 17 ]. Particularly in the last decade, different research groups have focused on the development of PLA/Ch materials [ 18 , 19 , 20 , 21 , 22 ]. Sébastien et al [ 18 ] and Grande and Carvalho [ 19 ] obtained composite films by solution mixing and film casting processes.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the antimicrobial performance of these films was not further evaluated [ 20 ]. Bonilla et al [ 21 ] and Chang et al [ 22 ] prepared chitosan–PLA films containing various amounts of chitosan by extrusion and demonstrated their antibacterial activity in refrigerated meat and fish samples, respectively.…”
Section: Introductionmentioning
confidence: 99%